Efficacy of Liposuction as a Delay Method for Improving Flap Survival - Orhan, Erkan; Erol, Yagmur Reyyan; Deren, Orgun; Altun, Serdar; Erdogan, Bulent (Springer, 2016)
Flaps are often used in repairing tissue defects and partial or full flap loss is still an important morbidity cause. Several techniques have been tried to increase flap circulation but none of these could replace the delay technique. Our goal in this study is to show the efficacy of liposuction in delay of dorsal rat cutaneous flaps and improvement in flap survival. Twenty-four Wistar rats were used. The rats in group 1 received 9 x 3-sized caudally-based random pattern skin flaps. In group 2, liposuction was done under the tissue island spotted as the flap and after 14 days, standard flap surgery was done. In group 3, surgical delay was done and after 14 days, standard flap surgery was done. In group 4, liposuction was done under the tissue island spotted as the flap and standard flap surgery was done right after the liposuction. The rate of necrotic tissue in group 3 (surgical delay; mean % 13.7) was less than the rate in group 2 (liposuction delay; mean % 15.1), although the difference was not statistically significant. The necrosis rates in group 3 (surgical delay) and group 2 (liposuction delay) were less than the rates in both group 1 (only flap; mean % 41.5) and group 4 (liposuction flap; mean % 40.0) and this difference was statistically significant (p < 0.0001). Liposuction can be an alternative to surgical delay as a less invasive method in the clinic. This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
Keywords: Flap; Delay; Liposuction